2019
DOI: 10.1024/0301-1526/a000752
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms for the effects of far-infrared on the cardiovascular system – a review

Abstract: Abstract. Far-infrared (FIR) is a form of thermal radiation, which may have beneficial effects on cardiovascular health. Clinical studies suggest that FIR irradiation may have therapeutic effects in heart failure, myocardial ischaemia and may improve flow and survival of arteriovenous fistula. Animal studies have suggested a wide range of potential mechanisms involving endothelial nitric oxide synthase and nitric oxide bioavailability, oxidative stress, heat shock proteins and endothelial precursor cells. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…After the IR source was removed, the venous flow diminished below the baseline. This positive effect of IR agrees with the results of previous studies (39,40).…”
Section: Resultssupporting
confidence: 93%
“…After the IR source was removed, the venous flow diminished below the baseline. This positive effect of IR agrees with the results of previous studies (39,40).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, FIR significantly prevented cisplatin‐evoked decreased capillary tube–like formation in HUVECs, while the event was strongly diminished by transfection with HIF‐1α siRNA, indicating the involvement of HIF‐1α in the proangiogenic activity of FIR. Previous studies have confirmed that FIR is able to alleviate ischemia/reperfusion injury and the poor blood flow in ischemic hindlimb of diabetic mice by enhancing endothelial progenitor cell functions and activating eNOS/NO cascade 29–31 . Accordingly, FIR has a therapeutic potential for ischemia‐associated cardiovascular diseases by augmenting HIF‐1α–dependent new vessel formation and vasodilation.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have confirmed that far‐infrared radiation (FIR) exhibits a protective effect against cardiovascular disorders and endothelial inflammation via heme oxygenase‐1 induction 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that far-infrared mechanisms include the activation of oxidative stress and heat shock proteins. Clinical studies have shown that FIR may have therapeutic effects on heart failure and myocardial ischemia and may improve the flow rate and survival rate of arteriovenous fistulas [ 25 ], implying that FIR may have a certain recovery effect on inflammation injury in living organisms. Proteomics research methods were adopted to further explain the mechanism of the SEW and FIR intervention.…”
Section: Discussionmentioning
confidence: 99%